How does internet usage affect the credit consumption among Chinese college students? A mediation model of social comparison and materialism. Issue 3 (12th November 2020) - Zhu, Xiaowen; Ren, Wei; Chen, Qiang; Evans, Richard
Abstract : Purpose: The use of consumer credit by Chinese citizens has risen rapidly in the Internet era. The purpose of this paper is to predict a mechanism for credit consumption through Internet usage, with social comparison and materialism as mediators. Four types of Internet usage (social use, entertainment use, informational use, and online shopping) were identified to investigate whether different types of Internet usage influence credit consumption differently and whether the influencing mechanisms vary. Design/methodology/approach: A structured online survey involving 558 valid responses from Chinese college students was completed, with structural equation modeling being applied to analyze the collected data. Findings: Among the four types of Internet activities, online shopping was found to be the most significant predictor of credit consumption; results show that it influences credit consumption through two indirect pathways: materialism and a combination of social comparison and materialism. Social use was found to only affect credit consumption through materialism. In contrast, the influences of both informational use and entertainment use on credit consumption were insignificant. Originality/value: By testing the concurrent mediating effects of social comparison and materialism, this study broadens our understanding of how Internet usage and credit consumption are connected. While most studies empirically test overall Internet usage and focus on direct relationships, we identify four types of Internet activities and demonstrate the mechanisms by which different types of Internet usage influence credit consumption, and how consumption varies based on Internet activity.